2011
DOI: 10.1099/jmm.0.024083-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial hypermutation: clinical implications

Abstract: Heritable hypermutation in bacteria is mainly due to alterations in the methyl-directed mismatch repair (MMR) system. MMR-deficient strains have been described from several bacterial species, and all of the strains exhibit increased mutation frequency and recombination, which are important mechanisms for acquired drug resistance in bacteria. Antibiotics select for drug-resistant strains and refine resistance determinants on plasmids, thus stimulating DNA recombination via the MMR system. Antibiotics can also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 91 publications
1
75
0
1
Order By: Relevance
“…Bacteria undergoing antibiotic treatment or cancer cells exposed to chemotherapy are prime examples of cells exposed to stressful conditions. Therefore, hypermutation should be considered a risk for both the development of multidrug resistance in pathogenic bacteria (Hammerstrom et al, 2015; Jolivet-Gougeon et al, 2011; Blázquez, 2003; Chopra et al, 2003) and cancer relapses as recently shown (Wang et al, 2016). Targeting hypermutation could pave the way not only for the development of novel anti-cancer therapies, but also for containing the spread of multidrug tolerant pathogens and even for the generation of robust, stress-resistant strains for use in various industrial processes.…”
Section: Discussionmentioning
confidence: 94%
“…Bacteria undergoing antibiotic treatment or cancer cells exposed to chemotherapy are prime examples of cells exposed to stressful conditions. Therefore, hypermutation should be considered a risk for both the development of multidrug resistance in pathogenic bacteria (Hammerstrom et al, 2015; Jolivet-Gougeon et al, 2011; Blázquez, 2003; Chopra et al, 2003) and cancer relapses as recently shown (Wang et al, 2016). Targeting hypermutation could pave the way not only for the development of novel anti-cancer therapies, but also for containing the spread of multidrug tolerant pathogens and even for the generation of robust, stress-resistant strains for use in various industrial processes.…”
Section: Discussionmentioning
confidence: 94%
“…Molecular evolution can also vary temporally, as was recently reported for Yersinia pestis and hypothesized to reflect strong demographic fluctuations [39]. On a shorter time scale, modulation of DNA repair pathways can increase the substitution rate dramatically in a process called hypermutation, which has been shown to be adaptively important, for example to gain antibiotic resistance [40,41]. The life cycles of many infectious bacterial pathogens introduce further possible causes of temporal variation in evolutionary rates.…”
Section: Biological Complexitiesmentioning
confidence: 99%
“…This is potentially relevant outside the laboratory given that mutator bacteria are common in clinical settings, particularly in chronic infections (Oliver et al, 2000;Denamur et al, 2002), and are frequently associated with antibiotic resistance Baquero et al, 2005;Maciá et al, 2005). Crucially, the mutator phenotype of clinical isolates, including E. coli, is frequently because of mutations in mismatch repair genes including mutS (LeClerc et al, 1996;Chopra et al, 2003;Li et al, 2003;Jolivet-Gougeon et al, 2011), the same mechanism as in our experiments. Mutator No phage HK578 T4 Figure 6 Selective effect of an elevated mutation rate.…”
Section: Discussionmentioning
confidence: 76%